Kinematics Analysis and Simulation of the Cement Truck Loading Manipulator - Wu Jinyi; Huang Jinfeng; Liu Wanyu; Cui Jianguo (Jixie chuandong, 2015)
Aiming at the practical needs of the cement loading industry,a kind of bagged cement automatic loading machine is developed and designed. Besides a truck loading manipulator with the characteristic simple structure,fewer driving parts,easy to control is presented. Firstly,the overall structure scheme of the automatic loading machine and basic structure of loading manipulator based on parallel mechanism are introduced,the kinematics model of manipulator is established,the kinematics inverse solution of position,velocity and acceleration are obtained. On the basis of the motion trajectory planning of the manipulator end,through importing kinematics solution into the movement simulation software Matlab,the kinematics simulation calculation is carried out,the mechanism change of position,velocity and acceleration curve are drawn out,a reference for the mechanical design and optimization of a manipulator mechanism and the type selection of drive servo motor is provided.